2021
DOI: 10.3390/cancers13040764
|View full text |Cite
|
Sign up to set email alerts
|

IRF8 Is an AML-Specific Susceptibility Factor That Regulates Signaling Pathways and Proliferation of AML Cells

Abstract: Personalized treatment of acute myeloid leukemia (AML) that target individual aberrations strongly improved the survival of AML patients. However, AML is still one of the most lethal cancer diseases of the 21st century, demonstrating the need to find novel drug targets and to explore alternative treatment strategies. Upon investigation of public perturbation data, we identified the transcription factor IRF8 as a novel AML-specific susceptibility gene in humans. IRF8 is upregulated in a subset of AML cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 88 publications
2
17
1
Order By: Relevance
“…Several recent reports have explored the roles of IRF8 and MEF2D in AML ( Cao et al 2021 ; Liss et al 2021 ; Zhao et al 2021 ). In Zhao et al (2021) , MEF2D is reported to inhibit a CEBPE-mediated program of leukemia differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports have explored the roles of IRF8 and MEF2D in AML ( Cao et al 2021 ; Liss et al 2021 ; Zhao et al 2021 ). In Zhao et al (2021) , MEF2D is reported to inhibit a CEBPE-mediated program of leukemia differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…As an orthogonal validation of the cell-type specificity of the TF regulons from GRaNIE eGRNs, we compared the regulons with differential expression data upon TF knockout (K/O) in the same cell type. We obtained data for one or two of the top five important TFs in each cell type: NFKB1 in macrophages (49), IRF8 in AML (50) and IRF1 and IRF2 in T-cells (44). The genes downregulated upon TF K/O were significantly enriched in the TF regulons of the respective cell types (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We obtained cell-type specific knock-out (K/O) data for THP1 derived macrophages (NFKB1) (49), the human AML cell line MV4-11 (IRF8) (50), and processed differential expression data from primary human CD4+ T cells (IRF1 and IRF2) (44). For the NKB1 and IRF8 datasets, raw sequencing files were obtained from GSE162015 and GSE163275 respectively, and data processing and quality control was performed with an in-house Snakemake pipeline as described previously (27).…”
Section: Methodsmentioning
confidence: 99%
“…Other authors have used publicly available data to identify essential factors for AML growth. In this sense, IRF8 was uncovered as an AML-specific susceptibility factor [ 83 ]. Using data uploaded in DepMap ( , accessed on 25 June 2022), the glutamine–cysteine ligase catalytic subunit ( GCLC ) was extracted as a fitness gene in AML cell growth, survival, clonogenicity and leukaemogenesis [ 84 ].…”
Section: Hematologic Dependency Map Through Crispr Screens: Essential...mentioning
confidence: 99%